The Effectiveness of Education Using Comic Books and Video Media on Knowledge and Skills in Menstrual Hygiene Management Among Adolescent Girls at SMP Negeri 6 Malang - Irene Aisha Selvira; Retno Dumilah (STIKes Budi Luhur Cimahi, 2026)
Menstrual hygiene management (MHM) education is needed to support adolescent girls in managing menstruation safely, confidently, and with dignity. This study compared comic book-based and video-based education for improving MHM knowledge and skills. A quasi-experimental two-group pretest–posttest design was used among 56 female students aged 12–14 years at SMP Negeri 6 Malang, selected through proportional stratified random sampling and divided equally between the video and comic book groups. Knowledge was measured using a researcher-modified questionnaire, and skills were assessed using an observation checklist. Paired-samples t-tests examined within-group changes, while independent-samples t-tests compared gain scores between groups. Knowledge improved in the video group by 26.19 points and in the comic book group by 23.33 points; the between-group difference was not significant (mean difference = 2.86, 95% CI -7.76 to 13.47; p = 0.592; Cohen's d = 0.14). Skills improved in the video group by 23.11 points and in the comic book group by 28.45 points; this difference was also not significant (mean difference = -5.34, 95% CI -16.48 to 5.79; p = 0.340; Cohen's d = -0.26). Both media were associated with significant short-term improvements within groups, but the statistical superiority of either medium was not demonstrated.